2003
DOI: 10.1046/j.1460-9592.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Due to Atrial Fibrillation in Hypertrophic Cardiomyopathy:

Abstract: FAVALE, S., et al.: Sudden Death Due to Atrial Fibrillation in Hypertrophic Cardiomyopathy: A Predictable Event in a Young Patient. This case refers to a 39‐year‐old woman with hypertrophic cardiomyopathy (HCM) and family history of sudden death (SD). In 1985, high rate atrial stimulation induced VF. In 1996 an ICD was implanted and she remained without arrhythmic events until November 2000 when the device reported one episode of atrial fibrillation degenerating into VF and terminated by the ICD. The VF induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5] The prevalence of AF has been reported to be 10-28% in HCM at 7-10 years after the initial diagnosis. 2,3,[34][35][36] The incidence of AF in the present series was almost identical to that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] The prevalence of AF has been reported to be 10-28% in HCM at 7-10 years after the initial diagnosis. 2,3,[34][35][36] The incidence of AF in the present series was almost identical to that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] It is well known that hemodynamic changes followed by sympathetic or parasympathetic activation play an important role in the triggering of AF. 6,7 Thomson et al reported that hypotension during central unloading might provide an additional or alternate trigger for arrhythmia in some patients with HCM.…”
mentioning
confidence: 99%
“…59,60 Rapid rates during AF may lead to hemodynamic deterioration with degeneration to ventricular fibrillation. 61,62 In contrast to most other conditions, AF may truly be a life-threatening arrhythmia in HCM.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Atrial fibrillation (AF) is a relatively common arrhythmia in patients with an implanted cardioverter defibrillator (ICD) 1–6 . Moreover, AF may favor the onset of ventricular tachyarrhythmias 7–11 . Dual‐chamber ICDs offer the possibility of monitoring, discriminating, and selectively treating both atrial and ventricular tachyarrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Moreover, AF may favor the onset of ventricular tachyarrhythmias. [7][8][9][10][11] Dual-chamber ICDs offer the possibility of monitoring, discriminating, and selectively treating both atrial and ventricular tachyarrhythmias. This has further increased interest in the characteristics of AF in this setting and in the complex interaction between atrial and ventricular tachyarrhythmias.…”
Section: Introductionmentioning
confidence: 99%